[Cystic formations of ovaries in women: clinical and morphological features] - Sorokina I.V.; Markovsky V.D.; Borzenkova I.V.; Kulakova E.A.; Myroshnychenko M.S.; Pliten O.N.; Myroshnychenko S.A. (Морфологія, 2015)
Background. Cystic formations of ovaries are an urgent problem of medicine due to the high incidence of these diseases in women, the difficulties of differential diagnosis and a high percentage of diagnostic and tactical mistakes leading to disruption of reproductive function. Objective: to identify the clinical and morphological features of cystic formations of ovaries in women of Kharkiv region on the basis of the analysis of archival material. Methods. The material of this study was archival materials of pathological anatomy department of The Municipal Health Care Institution «Regional Clinical Hospital – The Center of Emergency Medicine and Disaster Medicine» during 2013 y. 354 cases of histological examination of surgical material – deleted fragments of ovaries due to cystic formations or ovaries in complex with uterus and fallopian tubes due to leiomyoma of uterus – were analyzed. The slides, stained with hematoxylin and eosin, were studied on the microscope «Olympus BX-41». Digital data were processed using statistical methods of investigation. Results. 1. It was established that in women of Kharkiv region among all cystic formations of ovaries tumor-like processes (in order of frequency of occurrence – yellow bodies cysts, follicular cysts, simple cysts, endometrial cysts) occur 5.5 times more frequently in comparison with tumor processes (in order of frequency of occurrence – dermoid cysts, cystadenomas, cystadenocarcinoma). 2. Tumor and tumor-like cystic formations of ovaries occur 4.6 times more frequently in right ovary in comparison with the left. 3. Tumor and tumor-like cystic formations of ovaries were characterized by a certain age. Tumor-like cystic formations of ovaries were typical for younger women (average age of women – 31.03±0.49 year) and tumor cystic formations – for older women (average age of women – 37.70±1.53 years). Among all tumor-like cystic formations of ovaries yellow bodies cysts were typical for younger women, simple cysts – for older women. Among all tumor cystic formations of ovaries benign tumors (dermoid cyst, different variants of cystadenoma) were characteristic for younger women, malignant tumors of ovaries (cystadenocarcinoma) – for older women. Conclusion. These results confirm the relevance of the study: frequent occurrence of studied pathological processes, the young age of women with studied pathology, an opportunity to identify the pathological process at a younger age at the stage of benign growth and thus may prevent its transformation into a malignant tumor. Citation: Sorokina IV, Markovsky VD, Borzenkova IV, Kulakova EA, Myroshnychenko MS, Pliten ON, Myroshnychenko SA. [Cystic formations of ovaries in women: clinical and morphological features]. Morphologia. 2015;9(2):78-84. Russian.